Multidisciplinary Care for Cystic Fibrosis Liver Disease: Where Does the Adult Hepatologist Fit In?. Issue 5 (20th December 2019) - Ayoub, Fares; Li, Hechu; Blay, Charles; Trillo‐Alvarez, Cesar; Lascano, Jorge; Morelli, Giuseppe
Abstract : Watch a video presentation of this article